2020
DOI: 10.21203/rs.3.rs-43559/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Scaling-up Community Self-reporting Rate for COVID-19: Implication for Assessing the Perceived Stigmatization of COVID-19 Survivors Among Residents of Agege Local Government, Lagos, Nigeria

Abstract: Objective: Coronavirus disease 2019 (COVID-19) is an emerging public health problem with over two million confirmed infections globally. Previous studies show that stigma impede the response activities. Therefore, this study was conducted to assess the perceived stigmatization of COVID-19 survivors among residents of Agege local government, Lagos State, Nigeria. We conducted a cross-sectional survey among 333 consenting residents recruited from Agege local government using multi-stage sampling technique. An in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Stigma towards persons with COVID-19 has been experienced in many parts of the world. In a study carried out among residents in a locality in Lagos Nigeria to assess perceived stigmatization of survivors of COVID-19, almost half of the respondents admitted to stigmatizing survivors [21]. A qualitative study carried out in Ghana to assess the psychological distress and mental health disorders associated with COVID-19, revealed that many survivors and those suspectedto be infected had experienced stigma from family, health workers and others due to COVID-19 [22].…”
Section: Discussionmentioning
confidence: 99%
“…Stigma towards persons with COVID-19 has been experienced in many parts of the world. In a study carried out among residents in a locality in Lagos Nigeria to assess perceived stigmatization of survivors of COVID-19, almost half of the respondents admitted to stigmatizing survivors [21]. A qualitative study carried out in Ghana to assess the psychological distress and mental health disorders associated with COVID-19, revealed that many survivors and those suspectedto be infected had experienced stigma from family, health workers and others due to COVID-19 [22].…”
Section: Discussionmentioning
confidence: 99%